2019
DOI: 10.3889/oamjms.2019.369
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factor of Lower-limb Deep Vein Thrombosis after Major Orthopedic Surgery in Vietnamese Patients

Abstract: BACKGROUND: Deep venous thrombosis (DVT) is a prevalent complication of orthopedic surgery. According in many studies. The incidence of DVT may be up to 50% if thromboprophylaxis is not available. AIM: The objective of this study was to check the degree of disease, clinical characteristics and analyzed factors in vulnerabilities with lower-limp DVT after orthopedic surgery in a Vietnam teaching hospital. METHODS: Orthopedic patients who met criteria were recruited at our hospital between August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…While duration of surgery has been shown to be a risk factor in patients who develop VTE 10 , this risk factors is not universally accepted as a reliable metric for determining the overall risk of a patient for VTE. Several studies have shown that orthopaedic procedures which require postoperative immobilization put patients at an increased risk of developing symptomatic VTE 11,12 . Additionally, patients who are required to be non-weightbearing on their operative extremity have been shown to have increased incidence of VTE postoperatively 13 .…”
Section: - Concerning Vte Risk Which Surgeries Can Be Considered Majo...mentioning
confidence: 99%
“…While duration of surgery has been shown to be a risk factor in patients who develop VTE 10 , this risk factors is not universally accepted as a reliable metric for determining the overall risk of a patient for VTE. Several studies have shown that orthopaedic procedures which require postoperative immobilization put patients at an increased risk of developing symptomatic VTE 11,12 . Additionally, patients who are required to be non-weightbearing on their operative extremity have been shown to have increased incidence of VTE postoperatively 13 .…”
Section: - Concerning Vte Risk Which Surgeries Can Be Considered Majo...mentioning
confidence: 99%
“…Patients should be instructed t o keep an eye out for symptoms that point to DVT and to alert nurses if necessary. 4 Low-molecular-weight heparins, unfractionated heparin, and Fondaparinux are frequently used pharmacological agents for prophylaxis in medical patients. Mortality has been shown to be decreased by Direct oral anticoagulants (betrixaban versus subcutaneous enoxaparin).…”
Section: Introductionmentioning
confidence: 99%
“…50% of patients who were 50 years of age or older had deep vein thrombosis. 6 When compared to patients in the general hospitalized patients have a higher risk of developing VTE. Therefore, every hospitalized patient must take DVT prophylaxis into account.…”
Section: Introductionmentioning
confidence: 99%